Omnibus Law dalam Perspektif Hukum dan Politik - Miran, Miran; Lumban Tungkup, Doharman; Wira Perdana, Fadjrin; Irwan, Irwan; Setiono, Joko (Jurnal Indonesia Sosial Sains, 2022)
Omnibus law is a concept that is considered to be able to reduce state problems in the legal obesity aspect so that the government administration process becomes easier and has the ability to attract many foreign investors to improve people's welfare. For this reason, researchers want to find out more about omnibus law from a legal and political perspective. This research uses a descriptive qualitative type with data collection techniques using a normative juridical literature study. The results of the study show that omnibus law meets legal standards regarding the substance, structure and legal culture assessed from the legal aspect. Meanwhile, in the political field, it is known that the omnibus law has substance that is in accordance with the purpose of its formation as well as a long drafting process so that legal politics is carried out to facilitate the process of drafting up to the issuance of the Job Creation Act.